2021
DOI: 10.3390/v13102022
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Inflammatory Syndrome Following SARS-CoV-2 Infection in Children: One Year after the Onset of the Pandemic in a High-Incidence Area

Abstract: SARS-CoV-2 infection in children can trigger cardiovascular manifestations potentially requiring an intensive treatment and defining a new entity named Multisystem Inflammatory Syndrome in Children (MIS-C), whose features partially overlap with Kawasaki Disease (KD). A cross-sectional study including all diagnoses of MIS-C and KD from April 2020 to May 2021 in our metropolitan area was conducted evaluating clinical, laboratory (including immunological response, cytokines, and markers of myocardial damage), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 57 publications
3
44
0
1
Order By: Relevance
“…Additionally, patients have elevated inflammatory markers (CRP, procalcitonin, sedimentation, D-dimer, and ferritin) 1 17 22 23 and NT-proBNP. 1 10 16 Moreover, higher CRP, D-dimer, NT-proBNP, and lower lymphocyte count were detected in patients in the ICU. 24 In pediatric MIS-C case series, higher CRP and neutrophil counts as well as lower lymphocyte counts and albumin levels, were associated with children who developed shock.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Additionally, patients have elevated inflammatory markers (CRP, procalcitonin, sedimentation, D-dimer, and ferritin) 1 17 22 23 and NT-proBNP. 1 10 16 Moreover, higher CRP, D-dimer, NT-proBNP, and lower lymphocyte count were detected in patients in the ICU. 24 In pediatric MIS-C case series, higher CRP and neutrophil counts as well as lower lymphocyte counts and albumin levels, were associated with children who developed shock.…”
Section: Discussionmentioning
confidence: 96%
“…The Kawasaki disease is a childhood inflammatory disease and resembles MIS-C. 16 In studies conducted in children diagnosed with the Kawasaki syndrome, it was found that the patients with vitamin D levels of < 20 ng/mL were more resistant to IVIG treatment ( p = 0.023). 15 In the present study, most of our patients responded well to a single dose of the IVIG therapy (first-line treatment).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies focused on the recovery of MIS-C with follow-up for short-term ( 38 , 39 ), mid-term ( 19 , 40 , 41 ), and 1-year using conventional echocardiography ( 42 ). In total, 91.0% of patients with MIS-C had a normal LVEF by 30 days ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome can also be found in adult patients (MIS-A), usually four months after the acute phase of COVID-19, presenting with multiorgan dysfunction frequently requiring intensive care unit admission, while a minority of patients may present with Kawasaki disease [59]. It should be stressed, however, that prompt immunomodulatory treatment may lead to the regression of myocardial injury and the reversibility of left ventricular dysfunction [60].…”
Section: Coronavirus Disease-19-associated Vasculitidesmentioning
confidence: 99%